Modeling analysis of the effect of the main roll-hoop length on the strength of Formula Student chassis - Siswanto, Rudi; Subagyo, Rachmat; Isworo, Hajar; Gapsari, Femiana (Eastern-European Journal of Enterprise Technologies, 2019)
Chassis is a very important part of the vehicle, where the whole body of the vehicle is built. All vehicle external loads include their own weight supported by the chassis. Chassis design and analysis play an important role in making a vehicle. To find out the phenomenon of Formula Student Car, Autodesk Inventor simulation was made with variations in roll hoop length and static loading of 9, 6 and 5 kN. The chassis material is carbon steel which has a value of mechanical properties that meet regulatory standards. The results obtained in this study are the relationship between the main roll hoop length and normal stress and deflection is the same, the greater the value of the main roll hoop length, the greater the value of normal stress and deflection. The relationship between the main roll hoop length and normal stress is the greater the value of the main roll hoop length, the greater the normal stress value. While the relationship between the main roll hoop length and shear stress is the greater the value of the main roll hoop length, the lower the T-x shear stress value. The relationship between the main roll hoop length and normal stress and T-y shear stress is the same, namely the greater the value of the main roll hoop length, the higher the value of normal stress and shear stress T-y. The relationship between the main roll hoop length and normal stress is the greater the value of the main roll hoop length, the higher the normal stress and torsional value. Test results of normal stress, shear and torsional stress show that the chassis type B with a roll hoop height of 504 mm and the main roll hoop length of 125 mm meets the requirements.